Shopping Malls & Consequences on the Human Rights on Small Traders in NCR Delhi - Mullick, N. H. (Indian Journal of Marketing, 2012)
With the changing lifestyles, incomes and shopping habits, there is a lot of scope for organized retailing. Shopping malls are helping these retail giants by providing them the infrastructure required to grow fast. The present study is based on the multiple drivers of growth & the issues being faced today by these shopping malls, as their occupancy rate is decreasing day by day, and they are not able to find the right rentals due to reduction in the footfalls. So, the developers should position their property according to the profile of the customers present in the trade area. They must not act only as a realtor, because poor mall management has reduced the traffic of the malls and this has resulted in a low conversion rate (8-10% only). They must, therefore, research the area and then plan the tenant mix in their mall as per the target customers. Create Unique Selling Propositions (USP) for their malls and have the right rentals for their shopkeepers because high rentals will lead to less profit for the shop owners. The mall developer should also create an ambience and maintain a hygienic and a clean environment for family members to shop and have a good experience at the mall. This will only lead to a better experience for the whole family, and they will come again and again, resulting in better footfalls and profits for their shop owners in the future.